Effects of music, video, and 360‐degree video on cycle ergometer exercise at the ventilatory threshold - Bird, Jonathan M.; Karageorghis, Costas I.; Baker, Steven J.; Brookes, David A. (Scandinavian journal of medicine & science in sports, 2019)
Despite the seemingly ubiquitous presence of audiovisual stimuli in modern exercise facilities, there is a dearth of research examining the effects of audiovisual stimuli in combination during exercise. Accordingly, we examined the influence of a range of audiovisual stimuli on the improvement of affective, perceptual, and enjoyment responses to cycle ergometer exercise at the ventilatory threshold (VT), an intensity that is associated with the most affect‐related interindividual variability. A within‐subject design was employed, and participants (N = 18) completed a 25‐minute protocol that consisted of 2 minutes of seated rest, 5 minutes of warm‐up, 10 minutes of exercise at VT, 5 minutes of cooldown, and 3 minutes of seated rest. Participants exercised at VT under music, video, music‐video, 360‐degree video, 360‐degree video with music, and control conditions. The results revealed a condition × time interaction for perceived activation and a main effect of condition for state attention and perceived enjoyment. The 360‐degree video with music condition elicited the most positive affective valence, greatest perceived activation, most dissociative thoughts, and highest ratings of perceived enjoyment. The present findings indicate that audiovisual stimuli can influence affective, perceptual, and enjoyment responses to cycle ergometer exercise at the VT. Given the emerging support pertaining to a positive relationship between affective responses and exercise adherence, audiovisual stimuli, such as 360‐degree video with music, should be considered as a means by which to promote an enjoyable exercise experience.